Eosinophilic ascites: a diagnostic challenge. (6th September 2016) - Khalil, Hesham; Joseph, Moby
Abstract : Eosinophilic ascites is a rare feature of eosinophilic gastroenteritis. We would like to highlight this increasingly recognised diagnosis in a case of unexplained ascites. We present a challenging case of a woman aged 25 years who presented with nausea, vomiting, diarrhoea, generalised abdominal pain and swelling 8-week following delivery of her first baby. Her symptoms were primarily aggravated by eating, and she had also noticed postprandial itching and self-limiting generalised rash. She had a strong history of atopy. Physical examination revealed abdominal tenderness and distension with shifting dullness. Urticarial skin rash was noted on the face, neck, chest and abdomen. Routine biochemistry was normal apart from peripheral eosinophilia. Imaging confirmed moderate ascites. Diagnostic paracentesis showed exudative ascites with numerous eosinophils. Histology of the upper and lower gastrointestinal tract showed infiltration of the oesophageogastroduodenal and rectosigmoid mucosa with eosinophils. The patient significantly improved following a course of steroids and six-food elimination diet.